Experiencias del cuidador informal con Adultos Mayores con Discapacidad Auditiva. Centro de Salud Chimbo periodo diciembre 2022-abril2023 - Chico Gallo, Jefferson Lizandro (2023)
Introduction: The study seeks to explore the experiences of informal caregivers of hearing impaired older adults at Chimbo Health Center during a specific period. Caring for hearing impaired older adults can be a difficult and stressful task that can affect the caregiver's life. Purpose: To learn about the experiences of informal caregivers of older adults with hearing impairment, through an in- depth interview that helps to understand from the nursing perspective the experiential context of informal family caregivers. Methodology: The research is of a qualitative phenomenological type seeking to understand the personal experience of the individual, in this case, the informal caregivers of older adults with hearing impairment in a Health Center. A structured interview with 10 questions and ATLAS TI software will be used for data analysis, Results: three core categories were generated from the primary documents; Perception of the role of family caregiver, Personal experiences and Emotional experiences, with 10 subcategories and 4 analysis networks. Conclusions: it was found that caregiving is a challenge that requires a lot of dedication, strength and patience, and that caregivers need more support and resources. The caregiving role can be emotionally and physically demanding, with significant changes in the caregiver's life, but it can also be an opportunity to acquire new skills useful for overall health care. Caregivers experience a variety of negative emotions, but mutual support in the family can help to cope and strengthen family relationships. Key words: Elderly Informal Caregiver, Phenomenological Study, Hearing Impairment